Marketing mix y las ventas en la empresa CHU de Iquitos 2024 - Cahuaza Vasquez, Charli Luis (2025)
The research conducted at the CHU company in Iquitos during 2024 aimed to understand how marketing decisions relate to sales, a vital aspect for the growth and sustainability of the business. With a quantitative approach and without directly intervening in the company's actions, data were analyzed that revealed a very strong and positive connection between the marketing mix and sales behavior, with a correlation coefficient of 0.889 and a very high level of statistical confidence. This finding shows us that when the company manages the four pillars of marketing—product, price, place, and promotion—well, it not only improves its commercial results but also better satisfies its customers. This study not only confirms the importance of these practices but also encourages the company's managers to continue refining their tactics to remain competitive and respond to the changing needs of the market. Thus, the research becomes a practical and reliable guide for CHU and other companies in the sector to make informed decisions focused on growing and strengthening the relationship with their customers, understanding that behind every number there are people who value quality, fair price, accessibility, and effective communication.